Dinâmica territorial e seus rebatimentos na organização regional do estado de São Paulo - Claudio Antonio Gonçalves Egler; Vagner de Carvalho Bessa; André de Freitas Gonçalves (Confins)
Territorial dynamics and its repercussions on regional organization of the state of São Paulo- In this study, the territorial dynamics and its repercussions on regional organization of the state of São Paulo will be analyzed demographic, economic and social changes that allow a reflection about the recent territorial dynamics state of São Paulo. It will also be analyzed according to three basic scales: global, national and regional or intrastate. The purpose of this article is to interpret, by means of a multi-scale technique, complexity of the spatial processes that contribute to the differentiation of the territory state of São Paulo into regions. This differentiation will be the subject of a territorial subdivision of the state according with the strategy of territorial cohesion, sustainability and polycentricity. At the end there will be a brief prospective analysis for understanding the dynamics of territorial processes.